Multimodal assessment of treatment with proprotein convertase subtilisin/kexin type 9 inhibitors combined with statins for regulating coronary artery plaque regression in patients with chronic/acute coronary syndrome: A meta-analysis - Dexiao Yuan; Ting Cheng; Zhihua Cao; Fang Wang; Yongpeng Wang (Journal of International Medical Research)
Background Statins are the standard treatment for coronary atherosclerosis; however, some patients require additional therapies for optimal plaque regression. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors (PCSK9i), including monoclonal antibodies and small interfering RNA-based therapies, have shown promise as adjuncts to statins, although their efficacy for coronary plaque regression, as assessed by intravascular imaging, remains uncertain. Methods We conducted a meta-analysis to compare the treatment efficacy of statins combined with PCSK9i (PCSK9i group) versus statins alone or statins combined with placebo (control group) in adults with coronary atherosclerosis (INPLASY registration number: INPLASY202550027). Plaque lesions were assessed using intravascular ultrasound, optical coherence tomography, coronary computed tomography angiography, and near-infrared spectroscopy. Lipid profile parameters, including low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and lipoprotein(a), were measured and analyzed. Results In total, 11 trials involving 2490 patients (follow-up duration: 12–78 weeks) were included. Meta-regression showed that combination therapy significantly reversed coronary artery plaque ( p  < 0.001). No significant difference was observed in the atheroma volume between the PCSK9i and control groups; however, fibrous cap thickness increased significantly in the PCSK9i group. Additionally, low-density lipoprotein cholesterol and lipoprotein(a) levels decreased, while high-density lipoprotein cholesterol levels increased after PCSK9i treatment. Conclusion PCSK9i combined with statins effectively promote coronary plaque regression, particularly in patients with acute myocardial infarction, offering a promising approach for managing coronary atherosclerosis.